Pitfalls and fatal complications after iterative endoscopic retrograde cholangiopancreatography or percutaneous transhepatic cholangiography management of biliary tract cysts. When to do open surgery (cyst resection; hepaticojejunostomy) or liver transplant? - Andrea Cariati; Giuliano Bottino; Pietro Diviacco; Antonella De Negri; Eva Moraglia; Valerio Belgrano; Irene Leale; Elisa Piromalli; Rosario Fornaro; Mauro Nahun; Enzo Andorno. (Archives of Clinical and Experimental Surgery, 2016)
Biliary tract cysts are a group of rare congenital diseases that have been classified by Todani in 8 types. Hepaticojejunostomy has been the preferred intervention for Type I and IV biliary cysts. It has been postulated that, due to the low incidence of cancerization of Types II and III biliary cysts, a less invasive approach could be suggested, namely cyst resection in Type II, and endoscopic sphincterotomy with opening of choledochocele in small (<3 cm) Type III cysts from old patients. Moreover, Caroli disease has been proposed to be treated by percutaneous biliary drainages. The aim of the present study is to propose the therapeutics strategies to follow for the management of biliary tract cysts, in case of failure of percutaneous transhepatic cholangiography (PTC) and endoscopic retrograde cholangiopancreatography (ERCP). From 2008 to May 2014, three patients with congenital biliary tract cysts were followed. Two patients were found to be affected by bilateral liver Caroli disease and another young patient was found to be affected by a Type III biliary cyst (choledochocele). Patients affected by Caroli disease presented cholangitis, jaundice and fever and have been submitted to PTC. PTC, after an initial brief relief of the symptoms, failed in both cases. One of these patients with recurrent post PTC cholangitis was then successfully treated by orthotopic liver transplant. The other patient affected by Caroli disease died after multiple PTC. The young patient affected by choledochocele suffered from pancreatitis and jaundice and was submitted to ERCP. Endoscopic resection of choledochocele was followed by hemorrhagia and a fatal fungal sepsis. Minimally invasive approaches have been widely used in the management of biliary tract cysts. Diffuse bilateral Caroli disease of the liver can be initially managed by percutaneous drainage but if cholangitis recurs, in our opinion, it is useful to consider an open surgery procedure such as orthotopic liver transplant. Type III biliary cyst (choledococele) can be managed by ERCP if patient is old and the cyst is small (<3 cm) but when the cyst is larger than 3 cm, symptomatic, and the patient is young, one approach to take into consideration is open duodenostomy with choledochocele resection and reimplantation of the common bile and of Wirsung ducts into the duodenal mucosa. [Arch Clin Exp Surg 2016; 5(2.000): 128-133]